Standardization of prophylactic platelet transfusion dosing in a pediatric oncology population: a quality improvement project. Issue 12 (27th September 2018) - Leibowitz, Michael; Wolfe, Heather; Flynn, Andrea; Waanders, Angela; Burlingame, Caroline; Aumaier, Brenna; Friedman, David; Lambert, Michele P.
Abstract : BACKGROUND: Oncology patients are frequent recipients of prophylactic platelet transfusions. Recent studies have demonstrated that lower prophylactic doses of platelets were not associated with a higher incidence of bleeding. At our institution, we found wide variation in platelet dosing due to lack of guidance and support for standardized dosing. STUDY DESIGN AND METHODS: A collaborative process improvement project between oncology, hematology, intensivists, and the transfusion service established guidelines for dosing of prophylactic platelet transfusions in nonbleeding oncology patients: 10 mL/kg or less of apheresis platelets for patients weighing up to 20 kg and 1 unit of apheresis platelets patients weighing 20 kg or more, with our stated goal of standardizing transfusion practice. A graphic data display tool that draws on the electronic medical record to monitor platelet ordering was created, with a target goal of greater than 80% compliance with the dosing guidelines. We implemented decision support for dosing consistent with the guideline, and provided educational materials to prescribers at various levels of training within oncology over multiple plan‐do‐study‐act cycles. RESULTS: We were able to consistently achieve between 85 and 90% compliance of prophylactic platelet transfusion orders without an increase in the number of emergency department visits for bleeding or platelet transfusions or changing the time between platelet transfusions after guideline implementation. CONCLUSION: This project demonstrates that reducing the volume of prophylactic platelet transfusions to doses consistent with published studies was safe and that a process of guideline consensus based on published studies, well‐designed decision support for computerized physician order entry, and targeted educational efforts, were effective in changing practice at a large academic hospital.